2017
DOI: 10.1039/c6ra25420a
|View full text |Cite
|
Sign up to set email alerts
|

NMR spectroscopy study on N,N′-bismaleimide-4,4′-diphenylmethane and barbituric acid synthesis reaction mechanism in N,N′-dimethylformamide solvent

Abstract: 1H signal assignments of C1N0E, C1N0K, C2N0A, C2N0S model products of Michael addition reaction in STOBA-like synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…Wen et al [70] used nuclear magnetic resonance spectroscopy to conduct a study in the in situ setting and measure the equilibrium thermodynamics of the STOBA fabrication process. They researched the STOBA synthesizing procedure to identify important reactant locations, activation processes, and the effect of elements including the molecular level of the solution, the kind of reactant, the ratio, the volume, the activation time, the reaction duration, and the sequence of inclusion.…”
Section: Optimization Of Stoba Materials For Libsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wen et al [70] used nuclear magnetic resonance spectroscopy to conduct a study in the in situ setting and measure the equilibrium thermodynamics of the STOBA fabrication process. They researched the STOBA synthesizing procedure to identify important reactant locations, activation processes, and the effect of elements including the molecular level of the solution, the kind of reactant, the ratio, the volume, the activation time, the reaction duration, and the sequence of inclusion.…”
Section: Optimization Of Stoba Materials For Libsmentioning
confidence: 99%
“…They researched the STOBA synthesizing procedure to identify important reactant locations, activation processes, and the effect of elements including the molecular level of the solution, the kind of reactant, the ratio, the volume, the activation time, the reaction duration, and the sequence of inclusion. Figure 11 [70] showed that the STOBA synthesis reaction follows primarily the Michael addition process, specifically a 2 + 2 stepwise polymerization. The a-methylene carbon as well as the two amino nitrogen atoms of benzene-1,3,5-tricarbaldehyde (BTA) are possible locations for nucleophiles that respond to the electrophilic C of N,N ′ -bismaleimide-4,4 ′ -diphenylmethane.…”
Section: Optimization Of Stoba Materials For Libsmentioning
confidence: 99%